Process Integration for Hybrid Power System supply planning and demand management â A review - Mohammad Rozali, N.E. (Elsevier Ltd, 2016)
Modeling tools for the optimal Hybrid Power Systems (HPS) supply planning and demand management have been relatively established. However, complementary tools that can provide planners, decizion-makers, energy managers and electrical as well as power engineers with graphical and visualization insights that are vital for better conceptual understanding of the problems, particularly at the onset of hybrid power systems planning and design, have just been developed over the last five years. This paper reviews the six-year development of the insight-based graphical and algebraic Process Integration (PI) tools for the optimal HPS supply planning and demand management, i.e., from its inception in the year 2011, until 2016. Known as the Power Pinch Analysis (PoPA), the tool has been among the next-generation PI techniques for resource conservation following the developments of the heat, mass, water, gas, materials, property, solid and carbon emission pinch analysis techniques. This paper discusses the progress, challenges and contributions of PoPA in promoting Renewable Energy (RE) utilization in HPS. Case studies on implementation of PoPA for HPS planning and design presented in the paper show encouraging improvement on HPS profitability and reliability. Â© 2016 Elsevier Ltd